2004
DOI: 10.1037/0894-4105.18.3.450
|View full text |Cite
|
Sign up to set email alerts
|

Allocentric Spatial Memory Activation of the Hippocampal Formation Measured With fMRI.

Abstract: Hippocampal activation was investigated, comparing allocentric and egocentric spatial memory. Healthy participants were immersed in a virtual reality circular arena, with pattern-rendered walls. In a viewpoint-independent task, they moved toward a pole, which was then removed. They were relocated to another position and had to move to the prior location of the pole. For viewpoint-dependent memory, the participants were not moved to a new starting point, but the patterns were rotated to prevent them from indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
78
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 64 publications
7
78
0
2
Order By: Relevance
“…Recent experiments demonstrate that selective hippocampal damage prevents spatial relational learning in freely moving adult rhesus monkeys (Macaca mulatta) 7 . Studies of human hippocampal function also highlight its involvement with allocentric representations of space [8][9][10][11][12] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments demonstrate that selective hippocampal damage prevents spatial relational learning in freely moving adult rhesus monkeys (Macaca mulatta) 7 . Studies of human hippocampal function also highlight its involvement with allocentric representations of space [8][9][10][11][12] .…”
mentioning
confidence: 99%
“…Recent experiments demonstrate that selective hippocampal damage prevents spatial relational learning in freely moving adult rhesus monkeys (Macaca mulatta) 7 . Studies of human hippocampal function also highlight its involvement with allocentric representations of space [8][9][10][11][12] .Here, we tested the ability of juvenile monkeys that received hippocampal lesions shortly after birth to learn new spatial relational information. Freely moving monkeys were allowed to forage for a preferred food that was hidden beneath cups distributed in an openfield arena (Fig.…”
mentioning
confidence: 99%
“…self-ordered sequencing | muscimol | temporal lobe | cognition | nonhuman primate A lthough a role for the hippocampus in navigational spatial memory has been well documented in many species, including humans (1)(2)(3)(4), rodents (5,6), and monkeys (7)(8)(9), a role for hippocampus in nonnavigational spatial memory is less certain. Because nonhuman primates have a close neuroanatomical and behavioral homology to humans, they offer a unique opportunity to assess the neural substrates of spatial memory using nonnavigational tasks.…”
mentioning
confidence: 99%
“…By combining virtual reality and fMRI it has been shown that the Arena task reliably activates the hippocampus in a predictable way 20 . In this task both age and the muscarinic receptor antagonist, scopolamine, reduce hippocampal activation and impair spatial learning.…”
Section: P1vital Consortium Studies In Cognitive Disordersmentioning
confidence: 99%